1980
DOI: 10.1177/073998638000200406
|View full text |Cite
|
Sign up to set email alerts
|

Achieved Reading Level, Self-Esteem, and Grades as Related to Length of Exposure to Bilingual Education

Abstract: A quasi-experimental design was used to compare two groups of Mexican American seventh-grade students enrolled in a tra ditional junior high school where all subjects of the curriculum were presented in English. The experimental group (N = 86) had previously been taught for 1 or more years in an elementary bilingual program. The control group (N = 90) consisted of students who had attended a traditional elementary program in which all subjects were presented in English. The dependent variables examined for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Because the bilingual children were primarily taught in their native language in K–1 and the immersion children were taught in English, their pretests in second grade would surely have been affected by their different treatment before pretesting. Additional studies of this kind include those by Curiel, Stenning, and Cooper-Stenning (1980) and Thomas and Collier (2002). Meyer and Fienberg (1992, p. 24) noted the same problem with reference to the widely cited Ramirez, Pasta, Yuen, Billings, and Ramey (1991) study, which also obtained pretests after students had been in bilingual or English-only programs: “It is like watching a baseball game beginning in the fifth inning: If you are not told the score from the previous innings, nothing you see can tell you who is winning the game.” Studies that tested children in upper elementary or secondary grades who had experienced bilingual or English-immersion programs in earlier years were included if premeasures were available from before the programs began, but in most cases such premeasures were not reported, so there is no way to know if the groups were equivalent beforehand.…”
Section: Inclusion Criteria: Language Of Instructionmentioning
confidence: 99%
“…Because the bilingual children were primarily taught in their native language in K–1 and the immersion children were taught in English, their pretests in second grade would surely have been affected by their different treatment before pretesting. Additional studies of this kind include those by Curiel, Stenning, and Cooper-Stenning (1980) and Thomas and Collier (2002). Meyer and Fienberg (1992, p. 24) noted the same problem with reference to the widely cited Ramirez, Pasta, Yuen, Billings, and Ramey (1991) study, which also obtained pretests after students had been in bilingual or English-only programs: “It is like watching a baseball game beginning in the fifth inning: If you are not told the score from the previous innings, nothing you see can tell you who is winning the game.” Studies that tested children in upper elementary or secondary grades who had experienced bilingual or English-immersion programs in earlier years were included if premeasures were available from before the programs began, but in most cases such premeasures were not reported, so there is no way to know if the groups were equivalent beforehand.…”
Section: Inclusion Criteria: Language Of Instructionmentioning
confidence: 99%
“…Similarly, several studies tested children in upper elementary or secondary grades who had experienced bilingual or immersion programs in earlier years. These studies were included if premeasures were available from before the programs began, but in most cases such premeasures were not reported, so there was no way to know if the groups were equivalent beforehand (e.g., Thomas & Collier, 2002;Curiel, Stenning, & Cooper-Stenning, 1980).…”
Section: Criteria For Inclusionmentioning
confidence: 99%
“…Furthermore, many studies included by Rossell and Baker lacked any information about the initial comparability of children who experienced bilingual or English-only instruction (e.g., Matthews, 1979). These include studies that retroactively compared secondary students who had participated in bilingual or English-only programs in elementary schools but failed to obtain measures of early academic ability or performance (e.g., Powers, 1978;Curiel et al, 1980). Other studies compared obviously noncomparable groups.…”
Section: Previous Quantitative Reviewsmentioning
confidence: 99%
“…This instructional model is very different from structured immersion as used in the United States. Moreover, Slavin and Cheung (2003) pointed out that Rossell and Baker assigned multiple "votes" to studies that were published in multiple forms (Curiel, 1979;Curiel, Stenning, & Cooper-Stenning, 1980; El Paso Independent School District Office for Research and Evaluation, 1987, 1992, even though only one experiment was collectively reported. It should be noted that the studies assigned multiple votes presented results that Rossell and Baker (1996) interpreted as favoring immersion.…”
Section: Previous Research Synthesesmentioning
confidence: 99%